Effect Ecological Range Land Management on Livestock Production of Settled Nomads in the Bakkan Region of Southeran Iran - Bajdian, Gholam Reza (2005)
The Nomad Production System (NPS) in Bakkan covers four new villages (RSNs), two old villages (PSNs) and other nomads who migrate yearly (NSN). The NPS has two major. sub-systems, namely, the Cropland Production System (CPS) and the highland Range Production System (hRPS). These systems are linked together by grazing energy intake models of the sheep and goats under the NPS. This study focused on the identification and analysis of the components of the NPS during one complete year in the Bakkan distinct, located in Southern Iran. Therefore, the objectives of the study are: (1) To identify and describe the current components of a hRPS and their interactions; (2) To analyze CPS and its components as an alternative option to increase the yield and efficiency of rangeland production, considering the impact of water availability; (3) To identify the components of a grazing ruminant production system and their interactions; (4) To estimate and analyze changes in the distribution of croplandlrangeland income by farm size, and changes in rangeland allocation as a result of nomadic settlement; and finally (5) To evaluate the implications of the nomads' decisions on resource use. Based on the study objectives, an approach system was determined to be the best way of recognizing the effects of, and the relationships between the components. Since nomads are the main part of this dynamic system, modeling and simulating them is the most effective way to study and assess this complex system. Economic evaluation was another part of the study that was done based on a costbenefit analysis method. Surveys were used as a technique to gather data, from interviews with nomads and the heads of their groups over a period of six months. The GIS tool helped to prepare different layers of features and attributes of the Proper Use Factors (PUF) model to show the integrated components of the PUF model in the Available Forage (AF) of highland Range Production System. In conclusion, it was found that NSN, during wet and drought years, have a proportion of 9-10% of the whole production capacity in Bakkan. NSN have good pasture lands with proper condition and trend, and with suitable soil and slope properties. RSNs have a proportion of 53-57% of the whole production capacity in Bakkan during wet and drought years. PSNl and PSN2, with about 26 years and 100 years of settlement in Bakkan, respectively, have more farming and animal husbandry experience in comparison to the RSNs. Therefore, they would be expected to have higher crop production rates, to use better range management techniques, and to observe proper canying capacity (CC) limits in comparison with the others. These observations validate the generalized structure of the energy utilization models of grazing sheep under the different feeding and production systems, and these models -. can be coupled with the appropriate models of feeds and feeding systems in rangeland, cropland, and hand feeding systems. These results will enable the prediction of CC in any given situation under conditions similar to those in Bakkan. Finally, the sensitivity analysis used to derive the benefit/cost (BE) ratio of the project "with settlement", and with a longer sustainable life cycle, showed much less economic efficiency than the project "without settlement" due to the consideration of ecological effects in the former case. In the latest settlement project, it was seen that discounting effects are not noticeable unless environmental benefits significantly outweigh the influence of the cost savings benefit of the "without settlement" project. Keywords: Bakkan region, Ecological rangeland management, Livestock production, Settled nomads, Southern Iran.